2020
DOI: 10.1038/s41467-020-15896-4
|View full text |Cite
|
Sign up to set email alerts
|

Repressive chromatin modification underpins the long-term expression trend of a perennial flowering gene in nature

Abstract: Natural environments require organisms to possess robust mechanisms allowing responses to seasonal trends. In Arabidopsis halleri, the flowering regulator AhgFLC shows upregulation and downregulation phases along with long-term past temperature, but the underlying machinery remains elusive. Here, we investigate the seasonal dynamics of histone modifications, H3K27me3 and H3K4me3, at AhgFLC in a natural population. Our advanced modelling and transplant experiments reveal that H3K27me3-mediated chromatin regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 63 publications
2
40
0
Order By: Relevance
“…1). As previously defined 24 , the AhgFLC locus was classified into three regions: the nucleation region, the linker region, Reversion, leaf formation at the reproductive shoot apical meristem. In (b-i), temperature regimes are represented by grey lines (4 °C in cold and 20/15 °C D/N in warm, shown by the average value).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1). As previously defined 24 , the AhgFLC locus was classified into three regions: the nucleation region, the linker region, Reversion, leaf formation at the reproductive shoot apical meristem. In (b-i), temperature regimes are represented by grey lines (4 °C in cold and 20/15 °C D/N in warm, shown by the average value).…”
Section: Resultsmentioning
confidence: 99%
“…In A. halleri, the influence of DNA replication on the reduction of H3K27me3 would be minimal, given the fact that we analysed AhgFLC H3K27me3 levels in fully expanded leaves wherein cell division and endoreduplication are inactive 35,36 . We previously revealed that AhgFLC transcription starts earlier than the reduction of H3K27me3 at the locus 24 , which might trigger the active removal of the modification by recruiting H3K27me3 demethylases. Similar processes have been proposed as a candidate mechanism of Lov-1 AtFLC reactivation 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The next steps, in addition to the integration of GA signaling and its crosstalk with ABA, will be to provide information on temperaturemediated control of the regulatory cascades. Recent research led on Arabidopsis, allowed by highthroughput sequencing techniques, has hastened the pace for the incorporation of molecular data into phenology models (Satake et al 2013, Kudoh 2016, Antoniou-Kourounioti et al 2018, Nishio et al 2020), thus opening new roads for perennial studies.…”
Section: Towards New Phenology Approaches Based On Molecular Mechanismsmentioning
confidence: 99%